2020
DOI: 10.17582/journal.aavs/2021/9.4.462.472
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Theileriosis: Clinical, Pathological and Molecular Investigations

Abstract: Ovine theileriosis is a hemoprotazoan infection transmitted by tick bites which cause severe economic loss. This study aimed to survey Theileria infection of sheep in different localities of Egypt (Cairo, Giza and Al Monofia) by using microscopic and molecular detection associated with clinicopathological and pathological investigations. A total of 152 sheep blood samples were selected from farms and veterinary clinics. Microscopic examination of blood smears revealed that the incidence of Theileria infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
(33 reference statements)
0
8
0
1
Order By: Relevance
“… Cattle, humans, rodents ND Cairo, Menofia, Qena, Sinai [ [57] , [58] , [59] , [60] , [61] , [62] ] Hepatozoonosis Hepatozoon canis Dogs ND Cairo, Giza [ 63 , 64 ] Hepatozoon sp. Rodents ND Sinai [ 62 ] Theileriosis Theileria annulata Buffaloes, camels, cattle, sheep Hyalomma dromedarii, Hyalomma excavatum Aswan, Beheira, Benisuef, Dakahlia, Elminia, Fayoum, Giza, Menofia, New valley, Port Said, Qena, Qualyobia, Sharkia, Sohag [ 33 , 36 , [70] , [71] , [72] , [73] , [74] , 43 , 46 , 47 , [65] , [66] , [67] , [68] , [69] ] Theileria ovis Buffaloes, camel, cattle, equines, goats, sheep ND Aswan, Beheira, Benisuef, Cairo, Giza, Menofia, New valley, Qualyobia, Sinai [ 46 , 49 , 66 , 70 , 72 , [75] , [76] , [77] ] Theileria equi Donkey, horses, mules Rhipicephalus annulatus Alexandria, Benisuef, Cairo, Fayoum, Giza, Ismailia, Matrouh, Menofia [ 51 , …”
Section: Methodsmentioning
confidence: 99%
“… Cattle, humans, rodents ND Cairo, Menofia, Qena, Sinai [ [57] , [58] , [59] , [60] , [61] , [62] ] Hepatozoonosis Hepatozoon canis Dogs ND Cairo, Giza [ 63 , 64 ] Hepatozoon sp. Rodents ND Sinai [ 62 ] Theileriosis Theileria annulata Buffaloes, camels, cattle, sheep Hyalomma dromedarii, Hyalomma excavatum Aswan, Beheira, Benisuef, Dakahlia, Elminia, Fayoum, Giza, Menofia, New valley, Port Said, Qena, Qualyobia, Sharkia, Sohag [ 33 , 36 , [70] , [71] , [72] , [73] , [74] , 43 , 46 , 47 , [65] , [66] , [67] , [68] , [69] ] Theileria ovis Buffaloes, camel, cattle, equines, goats, sheep ND Aswan, Beheira, Benisuef, Cairo, Giza, Menofia, New valley, Qualyobia, Sinai [ 46 , 49 , 66 , 70 , 72 , [75] , [76] , [77] ] Theileria equi Donkey, horses, mules Rhipicephalus annulatus Alexandria, Benisuef, Cairo, Fayoum, Giza, Ismailia, Matrouh, Menofia [ 51 , …”
Section: Methodsmentioning
confidence: 99%
“…The The results of the phylogenetic tree of the local sequences of T. ovis was showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. ovis recorded in the NCBI GenBank for different countries including Pakistan and India, with the 100% Identity, after performing 100 nucleotide sequence reconstructing using Bootstrap analysis (Abid et al, 2021;Eliwa et al, 2021;Niaz et al, 2021). In addition, results of the phylogenetic tree of the local sequences of T. lestoquardi was also showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. lestoquardi recorded in the NCBI GenBank.…”
Section: Discussinmentioning
confidence: 99%
“…using c-PCR technique. This result is higher to the prevalence has been reported in other studies such as: in Mosul city and Basrah province, Iraq it was 0.03%, 17.5% in sheep using microscopic examination of stained blood smears respectively (Abood et al, 2005;Abdullah et al, 2019), in Kurdistan areas, Iraq it was 13.43% and 17.91% in sheep using microscopic examination and PCR techniques respectively (Hassen and Meerkhan, 2020), in Iran, Turkey, Sudan, and Pakistan it was 47.27%, 7%, 12.9%, and 24.6% respectively using PCR techniques (Khezri et al, 2016;Riaz and Tasawar, 2017;Lee et al, 2018;Benedicto et al, 2020), and in Egypt it was 21.7% using microscopic examination method (Eliwa et al, 2021). The reasons for the variance in the prevalence of Theileria spp.…”
Section: Discussinmentioning
confidence: 99%
See 2 more Smart Citations